The Use of Project Based Learning to Improve Students' Concept Understanding on Elasticity and Hooke Law - Safriana, Safriana; Nurlina, Nurlina; Ginting, Fajrul Wahdi; Badriah, Badriah (Universitas Syiah Kuala, 2022)
This study aims to determine the use of project-based learning models to improve students' conceptual understanding of elasticity and Hooke's law at SMA Negeri 1 Syamtalira Bayu. This research is a research quasi-experimental design. The sampling technique used is simple random sampling. The samples in this study were students of class XI IPA 4 as the control class with 27 students and class XI IPA 3 as the experimental class with 27 students. The results of the research data analysis showed that the N-Gain normalized obtained an average value of increasing understanding of the concepts of practical class students, namely 0.46 in the medium category, while the control class was 0.30 in the low sort. The test analysis results of the independent sample test for the experimental class and control class are 0.03 0.05. It can conclude that using learning models, project-based learning can improve students' understanding of concepts on elasticity and Hooke's law at SMA Negeri 1 Syamtalira Bayu.